`I always considered I needed injury prevention to become an elite athlete`: the road to the Olympics from the athlete and staff perspective - Bonell Monsonís, O.; Verhagen, E.; Kaux, J.-F.; Bolling, C. (BMJ Open Sport & Exercise Medicine, 2021)
In this study, we explored the perspectives about sports injury prevention of Belgium Olympic level athletes, coaches, managers and healthcare providers from various Olympic sports. We conducted a qualitative study, including 17 semistructured interviews. All interviews were transcribed verbatim and analysed by two independent coders through constant comparative data analysis based on Grounded Theory principles. Our findings overview the athlete`s journey to becoming an elite athlete, and how an elite sports context influences and modulates injury prevention practice at this level. Participants described an elite athletic career as a continuous and adaptive evolving process. According to athletes and all stakeholders, sports injury prevention is a learning process shaped by individual experiences. This embodiment provides athletes with insight into the importance of ownership of their bodies and self-awareness. Thus, experience, communication, empowerment, knowledge, education, the elite athlete context and sports culture, all play a fundamental role in sports injury prevention. Our findings support the importance of contextual factors in sports injury prevention in an elite sports context. These results also bring practical implications on how we should approach injury prevention differently along an athlete`s journey to becoming an elite athlete. Considering specific contextual factors and influencing the process through awareness, communication and a shared responsibility is essential to develop a healthy and successful athlete.